2016
DOI: 10.1039/c6ra06258j
|View full text |Cite
|
Sign up to set email alerts
|

Role of interfacial interactions to control the extent of wrapping of polymer chains on multi-walled carbon nanotubes

Abstract: Transmission electron microscopic image of separated MWCNTs (N51L15G5) showing the wrapped polymer chains on the MWCNTs surface, which corresponds to the α-phase of the PP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…It is reported earlier by us that Li‐AHA could “de‐agglomerate” efficiently MWCNTs via electrostatic charge repulsion between AHA ‐ and MWCNTs in deionized water. [ 18,20,45–47 ] Subsequently, on evaporation of deionized water, Li‐AHA physically encapsulated on smaller MWCNTs “agglomerate” and also on “individualized” MWCNT. The incorporation of increased concentration of Li‐AHA leads to a larger fraction of “individualized” MWCNTs and also open MWCNTs “agglomerate” structure of significantly smaller size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported earlier by us that Li‐AHA could “de‐agglomerate” efficiently MWCNTs via electrostatic charge repulsion between AHA ‐ and MWCNTs in deionized water. [ 18,20,45–47 ] Subsequently, on evaporation of deionized water, Li‐AHA physically encapsulated on smaller MWCNTs “agglomerate” and also on “individualized” MWCNT. The incorporation of increased concentration of Li‐AHA leads to a larger fraction of “individualized” MWCNTs and also open MWCNTs “agglomerate” structure of significantly smaller size.…”
Section: Resultsmentioning
confidence: 99%
“…[ 5–10 ] Subsequently, CNTs based PP composites were developed and reported, wherein single‐wall carbon nanotubes (SWCNTs) or multiwall carbon nanotubes (MWCNTs) were introduced during melt‐mixing. [ 11–22 ]…”
Section: Introductionmentioning
confidence: 99%
“…That suggests that CS and TritonX‐100 procect the MWCNTs surface, avoid further damage of MWCNTs structure. It was also found that when CS or TrintonX‐100 adhered on the MWCNTs surface, the D and G characteristic peaks of pristine MWCNTs upshifted and broadened because of a strong π–π interaction between CS or TrintonX‐100 and the MWCNTs . An upshift of about 7 cm −1 was also observed in the 2D band (around 2720 cm −1 ) of CS/MWCNTs, indicating a strong interaction between the MWCNTs and chitosan.…”
Section: Resultsmentioning
confidence: 99%
“…An upshift of about 7 cm −1 was also observed in the 2D band (around 2720 cm −1 ) of CS/MWCNTs, indicating a strong interaction between the MWCNTs and chitosan. It indicates that the existence of dispersants (CS or TrintonX‐100) may directly influence the vibrations of the carbon atoms in MWCNTs .…”
Section: Resultsmentioning
confidence: 99%
“…[ 15–17 ] In this connection, various efforts have been documented to enhance MWCNTs dispersion in PP matrix via the utilization of functionalized or non‐covalently modified MWCNTs along with PP‐g‐MA enhancing the interfacial interaction between PP and MWCNTs. [ 13,17,18 ]…”
Section: Introductionmentioning
confidence: 99%